Preliminary Tests, Phytochemical Investigation (GC/MS, HPLC), and Cytotoxic Activity of Pyrus calleryana Fruits Cultivated in Iraq - Dhuha A. Alshammaa; Noor S Jaafar (Iraqi Journal of Pharmaceutical Sciences, 2025)
Worldwide neither information is available regarding the chemical constituents of Pyrus calleryana fruits nor its pharmacological effects. Previous studies demonstrated that Pyrus is a rich source of phenolics and has various pharmacological actions. Therefore, this study aimed to identify the secondary metabolites, especially phenolic compounds, and isolate phenolic acids in addition to investigating the fruits’ cytotoxic effect. powdered fruits were defatted with hexane and hexane extract was subjected to GC/MS. the defatted fruits were extracted through reflex (80% ethanol), phytochemical tests were done, and then acidic hydrolysis for the extract. The hydrolyzed extract was subjected to sequential extraction using chloroform, ethyl acetate, and n.butanol. TLC was done for these fractions for the identification of phenolic acids and flavonoids. Phenolic acids were identified and isolated from ethyl acetate fraction using HPLC. MTT test was used to determine the cytotoxic effect of ethyl acetate fraction on the A549 cell line. GC/MS analysis revealed that fatty acids esters and fatty acids were the most predominant compounds in hexane extract. For the first time, two known phenolic acids: p.coumaric and caffeic acid were obtained and identified from the ethyl acetate fraction of this plant. This fraction demonstrated no cytotoxic on the A549 cell line (IC50 of ethyl acetate fraction was 245319 µg/ml). This is the first study demonstrating the phenolic profile of Pyrus calleryana fruits, qualitatively Ethyl acetate fraction was a rich source of phenolic compounds, and Pyrus fruits exert no cytotoxic effect, further studies are required to evaluate the cytotoxic effect of this plant using other assays.